ANALYSIS OF CHANGES IN OUTDOOR AIR TEMPERATURE IN UKRAINIAN REGIONS WITH SPECIAL FOCUS ON POSSIBLE EXTREME CONDITIONS - ДЕШКО, В. І.; БІЛОУС, І. Ю.; СУХОДУБ, І. О.; ГЕТМАНЧУК, Г. О.; КРАМАРЕНКО, С. O. (Technologies and Engineering, 2025)
The purpose of the article is to analyze outdoor temperature data from Ukraine's climatic databases and Meteonorm, using historical, current, and forecast data to assess the potential for utilizing renewable energy sources. The methodology includes the application of synthesis and analysis methods for climatic data. Findings an analysis of outdoor temperatures as climatic data that have the greatest impact on building energy efficiency and comfort provision. Special attention is paid to the analysis of extreme weather conditions, such as heatwaves, tropical nights, frost days, and cold days. The article compares regulatory and climatic data for historical and current periods, as well as future scenarios of outdoor temperature changes influenced by anthropogenic factors. It has been established that with each subsequent RCP scenario (RCP 2.6, RCP 4.5, RCP 8.5), there will be a faster increase in the average annual outdoor temperature. By 2100, outdoor temperatures in Kyiv are expected to rise by 1.2°C, 3.1°C, and 5.8°C, respectively, under RCP 2.6, RCP 4.5, and RCP 8.5 scenarios. In Odesa, the temperature increase by 2100 will amount to 1.1°C under RCP 2.6, 2.9°C under RCP 4.5, and 5.3°C under RCP 8.5. The results also indicate an increase in the number of heatwaves and tropical nights, alongside a reduction in the number of frost and cold days. Originality is the justification of the use of international climatic databases for the design of building energy supply systems using renewable energy sources in the context of climate change and the current regulatory climatology of Ukraine. The practical value of the research results allows us to assess the differences in the climate of different regions of Ukraine, their changes in the context of historical, current and future climate changes. Also, the article analyzes extreme weather data, which is relevant in the context of the design of engineering systems and building sources.